The Potential Threat of Artificial Intelligence Use in Cybercrime Activities: A Case Study of 2024 Regional Head Elections - Erlangga, Lytio Enggar; Rofii, Muhammad Syaroni; Daryanto, Eko (International Journal of Science and Society, 2024)
The adoption of artificial intelligence (AI) has significantly increased in recent years, offering both opportunities and challenges. While AI enhances efficiency across various sectors, it also introduces new risks, particularly in the realm of cybercrime. This study explores the potential threats posed by AI-driven cybercrime activities in the context of the 2024 Regional Head Elections (Pilkada) in Indonesia. Using a qualitative method with literature review and document analysis, the research identifies three key threat domains: cybersecurity, physical security, and political security. AI enables cybercriminals to launch sophisticated and hard-to-detect attacks, such as phishing, misinformation campaigns, and distributed denial-of-service (DDoS) attacks. These threats could disrupt electoral processes, manipulate voter behaviour, and compromise the integrity of election outcomes. The study highlights how AI-driven attacks can also exploit Internet of Things (IoT) devices and spread deepfakes and political bots to influence public perception. With the rapid advancement of AI, traditional cybersecurity measures may struggle to keep pace, making it imperative for authorities and cybersecurity experts to strengthen monitoring and response capabilities. This research emphasizes the need for robust strategies to mitigate AI-driven cyber threats and safeguard the integrity of the electoral process in Indonesia.